THE INFLUENCE OF SCRAMBLE MEDIA ON STUDENTS’ READING SKILLS - Nadia Rahmi; Rambe, Riris Nurkholidah (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2024)
Abstract Reading has a very important role in education, especially for students to obtain information, broaden their horizons, and sharpen their views. This study aimed to see the effect of using scramble media on students' reading skills in the high class of SD 067251. The research type used was quasi-experimental design. The sample consisted of students in class IVA as the control group and students in class IVB as the experimental group, selected using a purposive sampling technique. The research instruments used were oral tests (reading) and written tests (multiple choice) of 20 questions. The data analysis used was descriptive and inferential analyses using the Independent Sample t-test. The results showed that using scramble media had an effect on students' reading ability. This can be seen from the average score of students taught using scramble media, which is higher than the conventional media (books and blackboards). Scramble media can be considered as an alternative medium to help overcome students' reading disabilities, especially in high grades.